2005
DOI: 10.1103/physrevb.72.045423
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction peak profiles from threading dislocations in GaN epitaxial films

Abstract: We analyze the lineshape of x-ray diffraction profiles of GaN epitaxial layers with large densities of randomly distributed threading dislocations. The peaks are Gaussian only in the central, most intense part of the peak, while the tails obey a power law. The q −3 decay typical for random dislocations is observed in double-crystal rocking curves. The entire profile is well fitted by a restricted random dislocation distribution. The densities of both edge and screw threading dislocations and the ranges of disl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
212
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 201 publications
(244 citation statements)
references
References 42 publications
18
212
1
3
Order By: Relevance
“…Feng et al recently performed cross-sectional TEM analysis of m-plane In 0.26 Ga 0.74 N/GaN MQWs and found that BSFs are formed within the MQWs. 23 The stripe densities along [11][12][13][14][15][16][17][18][19][20] were also determined from both SEM and AFM images, which are of the order of 1-2 Â 10 5 cm À1 . This increase in the stripe densities along [11][12][13][14][15][16][17][18][19][20] is probably related to changes in the growth conditions required for higher InN incorporation in the MQWs.…”
Section: Fig 4 (A)-(d) Ecc Images Showing Tds and Striated Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Feng et al recently performed cross-sectional TEM analysis of m-plane In 0.26 Ga 0.74 N/GaN MQWs and found that BSFs are formed within the MQWs. 23 The stripe densities along [11][12][13][14][15][16][17][18][19][20] were also determined from both SEM and AFM images, which are of the order of 1-2 Â 10 5 cm À1 . This increase in the stripe densities along [11][12][13][14][15][16][17][18][19][20] is probably related to changes in the growth conditions required for higher InN incorporation in the MQWs.…”
Section: Fig 4 (A)-(d) Ecc Images Showing Tds and Striated Featuresmentioning
confidence: 99%
“…The density of the striated features along [11][12][13][14][15][16][17][18][19][20] and also the overall surface roughness increases with InN content. This makes it difficult to identify BSFs for samples with MQWs containing more than 5% InN.…”
Section: Fig 4 (A)-(d) Ecc Images Showing Tds and Striated Featuresmentioning
confidence: 99%
See 3 more Smart Citations